A Marine Actinomycete Rescues Caenorhabditis elegans from Pseudomonas aeruginosa Infection through Restitution of Lysozyme 7 - Fatin, Siti N.; Tan, Boon Khai; Chong, Alexander Shu Chien; Khairuddean, Melati; Abdullah, Amirul AI-Ashraf (Frontiers Media, 2017)
The resistance of Pseudomonas aeruginosa to conventional antimicrobial treatment is a major scourge in healthcare. Therefore, it is crucial that novel potent anti-infectives are discovered. The aim of the present study is to screen marine actinomycetes for chemical entities capable of overcoming P. aeruginosa infection through mechanisms involving anti-virulence or host immunity activities. A total of 18 actinomycetes isolates were sampled from marine sediment of Songsong Island, Kedah, Malaysia. Upon confirming that the methanolic crude extract of these isolates do not display direct bactericidal activities, they were tested for capacity to rescue Caenorhabditis elegans infected with P. aeruginosa strain PA14. A hexane partition of the extract from one isolate, designated as Streptomyces sp. CCB-PSK207, could promote the survival of PA14 infected worms by more than 60%. Partial 16S sequence analysis on this isolate showed identity of 99.79% with Streptomyces sundarbansensis. This partition did not impair feeding behavior of C. elegans worms. Tested on PA14, the partition also did not affect bacterial growth or its ability to colonize host gut. The production of biofilm, protease, and pyocyanin in PA14 were uninterrupted, although there was an increase in elastase production. In lys-7::GFP worms, this partition was shown to induce the expression of lysozyme 7, an important innate immunity defense molecule that was repressed during PA14 infection. GC-MS analysis of the bioactive fraction of Streptomyces sp. CCB-PSK207 revealed the presence of methyl esters of branched saturated fatty acids. In conclusion, this is the first report of a marine actinomycete producing metabolites capable of rescuing C. elegans from PA14 through a lys-7 mediated activity.